W kwestii metropolii i obszarów metropolitalnych - Szmytkie, Robert (Uniwersytet Wrocławski. Wydział, Prawa, Administracji i Ekonomii, 2013)
The aim of this paper is to determine the rank of large Polish cities in the network of global cities, and to systematize the criteria used to define metropolises and metropolitan areas. In the time of globalization the term „metropolis” became unusually popular. This specific trend resulted in a large number of Polish cities aspiring to become or to be called “metropolis”, irrespective of their performed functions.There is no consensus about the use or understanding of terms „metropolis” and„metropolitan area”. For this reason those terms are often applied exaggeratedly or incorrectly.The article discusses the application of those terms and their synonyms with regards to the problem of Polish cities.
Keywords: metropolia; metropolizacja; obszar metropolitalny